Assessing intrapersonal peacefulness: Validation and cultural adaptation of the Self-Perception Scale with Indonesian samples - Sahril Buchori; Nurfitriany Fakhri; Ria Andriany Fakhri (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
The study of intrapersonal peacefulness has begun to develop in Indonesia. However, there is no specific scale in the country that measures the concept as a personality trait. The primary aim of this research is to examine the psychometric characteristics of the Self-Perception Scale for the Indonesian context (SPS-I) with the purpose of validating and customizing it for the Indonesian setting. The study was conducted on 1552 adolescents (983 males and 569 females) in Indonesia. Exploratory factor analysis (EFA) was conducted, followed by confirmatory factor analysis (CFA), to evaluate the factor structure. The CFA results comprised 12 adequate items showing saturation factors ranging from 0.468 to 0.780. Measurement model fit (p < .01, TLI = .946, CFI = .956, RMSEA = .06, SRMR = .036). The construct reliability of the SPS-I was .865 (Cronbach's α) and .848 (McDonald's ω). The results suggest that the measuring tool demonstrated enhanced consistency, and the goodness of fit model produced a high score. The study introduces the novel notion of intrapersonal peacefulness as a personality trait, which can significantly contribute to the promotion of social competencies that value diversity and nonviolent methods of conflict resolution.